The Role of Married Women’s Labor Supply on Family Earnings Distribution in Japan - Abe, Yukiko; Oishi, Akiko S. (Journal of Income Distribution®, 2007)
In this article, we empirically examine the impact of wives’ participation in the labor market on family earnings inequality, by paying attention to the dynamic aspect of labor supply by wives. We find that wives’ earnings have a moderate equalizing effect on family earnings inequality. Unlike in the United States, cohort effects in earnings inequality are relatively small in Japan. The correlation between husbands’ and wives’ earnings is small for almost every cohort in our cross-sectional data. The analysis of panel data suggests that married women’s employment has a strong persistence, which has a significant impact on the level of family earnings.